Arte, técnica e ciência náutica no Portugal moderno : contributos da "sabedoria dos descobrimentos" para a ciência europeia - Polónia, Amélia (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article aims to discuss the extent to which technical and scientific knowledge resulting from the process of the Portuguese discoveries and overseas expansion was based, or not, on scientific procedures and praxes and whether it contributed, or not, to the construction of a new scientific system that came to mark Europe in the 17th century. To this end, we shall address in the first place the concepts and practices of the “art of navigating”, “naval technique” and “naval science” and, then proceed with some epistemological insights of the so-called “wisdom of the discoveries”. The considerations presented here are not drawn from original research on the topic under study, but merely from reflection on widely known data and information.